Microwave Impedance Spectroscopy and Temperature Effects on the Electrical Properties of Au/BN/C Interfaces - Hazem K. Khanfar; A. F. Qasrawi; Yasmeen Kh. Ghannam (Active and Passive Electronic Components)
In the current study, an Au/BN/C microwave back-to-back Schottky device is designed and characterized. The device morphology and roughness were evaluated by means of scanning electron and atomic force microscopy. As verified by the Richardson–Schottky current conduction transport mechanism which is well fitted to the experimental data, the temperature dependence of the current-voltage characteristics of the devices is dominated by the electric field assisted thermionic emission of charge carriers over a barrier height of ~0.87 eV and depletion region width of ~1.1 μm. Both the depletion width and barrier height followed an increasing trend with increasing temperature. On the other hand, the alternating current conductivity analysis which was carried out in the frequency range of 100–1400 MHz revealed the domination of the phonon assisted quantum mechanical tunneling (hopping) of charge carriers through correlated barriers (CBH). In addition, the impedance and power spectral studies carried out in the gigahertz-frequency domain revealed a resonance-antiresonance feature at frequency of  ~1.6 GHz. The microwave power spectra of this device revealed an ideal band stop filter of notch frequency of  ~1.6 GHz. The ac signal analysis of this device displays promising characteristics for using this device as wave traps.